Host response in aggressive periodontitis. (June 2014) - Kulkarni, Cyelee; Kinane, Denis F.
Abstract: It is critical to understand the underlying host responses in aggressive periodontitis to provide a better appreciation of the risk and susceptibility to this disease. Such knowledge may elucidate the etiology and susceptibility to aggressive periodontitis and directly influence treatment decisions and aid diagnosis. This review is timely in that several widely held tenets are now considered unsupportable, namely the concept that Aggregatibacter actinomycetemycomitans is the key pathogen and that chemotactic defects in polymorphonuclear leukocytes are part of the etiopathology. This review also serves to put into context key elements of the host response that may be implicated in the genetic background of aggressive periodontitis. Furthermore, key molecules unique to the host response in aggressive periodontitis may have diagnostic utility and be used in chairside clinical activity tests or as population screening markers. It is becoming increasingly appreciated that the microbial etiology of aggressive periodontitis and the histopathology of this disease are more similar to than different from that of chronic periodontitis. An important therapeutic consideration from the lack of support for A. actinomycetemycomitans as a critical pathogen here is that the widely held belief that tetracycline had a role in aggressive periodontitis therapy is now not supported and that antibiotics such as those used effectively in chronic periodontitis (metronidazole and amoxicillin) are not contraindicated. Furthermore, A. actinomycetemycomitans ‐related molecules, such as cytolethal distending toxin and leukotoxin, are less likely to have utility as diagnosis agents or as therapeutic targets.